Analysis of Fractional Order Computer Virus Model with Multiple Ways of Infections Potential - Akgül, Ali; Farman, Muhammad; Akram, Muhammad Mannan; Sajjad, Assad; Azeem, Muhammad (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we propose a novel technique for the computer virus epidemic which contains infected external computer effects and removable storage media on the computer viruses. The positivity and boundedness for validation of the model are also discussed. The existence and uniqueness of the system of solutions for the model are made by using fixed point theory and iterative method. Numerical simulation obtained with proposed scheme which shows the impacts of varying the fraction-al-order parameters and the support of the theoretical results.